2021
DOI: 10.3390/atmos12101271
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Characteristics of the Surface Urban Heat Island and Its Driving Factors Based on Local Climate Zones and Population in Beijing, China

Abstract: The increasing degree of urbanization has continuously aggravated the surface urban heat island (sUHI) effect in China. To investigate the correlation between spatiotemporal changes of sUHI and urbanization in Beijing, land surface temperature in summer from 2000 to 2017 and the distribution of local climate zones (LCZs) in 2003, 2005, 2010, and 2017 was retrieved using remote sensing data and used to analyze the sUHI area and intensity change. The statistical method GeoDetector was utilized to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…LCZ solutions can be classified into different types based on surface materials, ground cover, and the influence of human activities. A study by Zhang et al ( 67 ) on the temporal and spatial variability of UHI and urbanization in Beijing showed that LCZ conversion had a significant impact on surface UHII. In addition, Quan et al ( 68 ) conducted an LCZ classification of Beijing, combining MODIS data with wind and cloud data at 100 m; the results showed significant differences in the LCZ diurnal thermal response with seasonal changes.…”
Section: Discussionmentioning
confidence: 99%
“…LCZ solutions can be classified into different types based on surface materials, ground cover, and the influence of human activities. A study by Zhang et al ( 67 ) on the temporal and spatial variability of UHI and urbanization in Beijing showed that LCZ conversion had a significant impact on surface UHII. In addition, Quan et al ( 68 ) conducted an LCZ classification of Beijing, combining MODIS data with wind and cloud data at 100 m; the results showed significant differences in the LCZ diurnal thermal response with seasonal changes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, only [38] used another LCZ land cover class as a reference, which used class B, which means scattered trees with mostly pervious land. However, only using LCZ classes to improve the SUHI calculation is considered an improvement in the research's articles [5,39].…”
Section: Surface Urban Heat Island (Suhi) Calculationmentioning
confidence: 99%
“…Climate Zones (LCZ) arranges the different urban and rural areas in more detail. In addition, the LCZ has been increasingly used in urban heat islands studies [5]. It was initially proposed in 2012 when regional climate zones were divided into several local climate zones within cities according to different LULC surface types, consequently allowing the correlation between climate information and urban planning [6].…”
Section: Introductionmentioning
confidence: 99%
“…The surface UHI (SUHI) is monitored via land surface temperature values obtained from satellites such as LANDSAT 8 [6]. The UHI based on air temperatures (AUHI) is monitored using a network of ground-based temperature sensors from weather stations in urban and rural areas [7].…”
Section: Introductionmentioning
confidence: 99%